2020
DOI: 10.1002/ar.24465
|View full text |Cite
|
Sign up to set email alerts
|

Normal human macula densa morphology and cell turnover: A histological, ultrastructural, and immunohistochemical investigation

Abstract: The aim was to analyze the morphology of normal human macula densa (MD), evaluate the cells that may be responsible for its turnover, and collect quantitative data. Of four samples of normal human renal tissue, two were embedded in resin to measure the longitudinal extension and examine the ultrastructure of the MD, the other two were embedded in paraffin to study apoptosis and cell proliferation. The MD is composed of a monolayer tissue about 40 μm long, which includes 35-40 cells arranged in overlapping rows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 34 publications
0
6
2
Order By: Relevance
“…Future work is needed to dissect their roles in MD cells. The known structural and neuron-like functional heterogeneity between individual MD cells (7,11,35) was reflected also in their regenerative gene profile established by single-cell transcriptome analysis (Fig. 2C).…”
Section: Discussionmentioning
confidence: 88%
“…Future work is needed to dissect their roles in MD cells. The known structural and neuron-like functional heterogeneity between individual MD cells (7,11,35) was reflected also in their regenerative gene profile established by single-cell transcriptome analysis (Fig. 2C).…”
Section: Discussionmentioning
confidence: 88%
“…One‐hundred and forty‐nine podocytes were analysed and six were multinucleated (4%; 95%CI: 1.5%–8.6%) (Table 2). We suggest that these multinucleated cells can be considered as resident parenchymal cells that together with scattered tubular cells (Angelotti et al, 2012; Hansson et al, 2014; Kang et al, 2016; Lazzeri et al, 2018, 2019; Lindgren et al, 2011; Lorenzi et al, 2020; Rinkevich et al, 2014; Smeets et al, 2013) have the capacity to maintain renal tissue homeostasis. The presence of multinucleated cells has been previously demonstrated in the liver (Figure 3b) (Kudryavtsev et al, 1993; Wang et al, 2017) and polyploidy was demonstrated in accordance to the different grades of hepatocyte maturity, i.e.…”
Section: Resultsmentioning
confidence: 98%
“…The Avidin–Biotin-Complex with peroxidase method (ABC; Vector Laboratories) was performed for 1 h at RT, and 3-3′ diaminobenzidine hydrochloride (DAB; Sigma-Aldrich, St Louis, MO, USA) was used as chromogen. Normal human renal macula densa tissue was used as positive control for nNOS (Lorenzi et al 2020 ). Immunostained sections were inspected with a motorized Leica DM6000 microscope (Leica Microsystems, Wetzlar, Germany), using different magnifications (10×, 25× and 40×).…”
Section: Methodsmentioning
confidence: 99%